PENERAPAN MEDIA LAGU PADA MATA PELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KEMAMPUAN APRESIASI PUISI SISWA KELAS V SDN 11 KAMPUNG TERANDAM KECAMATAN KOTO XI TARUSAN - Jusnida Jusnida (JRTI (Jurnal Riset Tindakan Indonesia), 2016)
Indonesian language subject is one of substantial subjects that should be learned by students early. Poem reading is a part of Indonesian language subject emphasizing on giving the direct experiences. Generally, students get problem in improving skill of poem appreciating because it is a not concrete learning. This research was aimed to improve students’ skill of poem appreciating by using songs media. Data of research were obtained from test and observation. This research took place only in one cycle consisting of two meetings. After the cycle, mean score of students’ skill of poem appreciating become 88. Based on the research result, it can be concluded that implementation of songs media can improve skill of poem appreciating of  students grade V SDN 11 Kampung Terandam Koto XI Tarusan.